Chemical Diversity on Small Scales: Abundance Analysis of the Tucana V Ultrafaint Dwarf Galaxy - Terese T. Hansen; Joshua D. Simon; Ting S. Li; Domani Sharkey; Alexander P. Ji; Ian B. Thompson; Henrique M. Reggiani; Jhon Yana Galarza (The Astrophysical Journal, 2024)
The growing number of Milky Way satellites detected in recent years has introduced a new focus for stellar abundance analysis. Abundances of stars in satellites have been used to probe the nature of these systems and their chemical evolution. However, for most satellites, only centrally located stars have been examined. This paper presents an analysis of three stars in the Tucana V system, one in the inner region and two at ∼10′ (7–10 half-light radii) from the center. We find a remarkable chemical diversity between the stars. One star exhibits enhancements in rapid neutron-capture elements (an r -I star), and another is highly enhanced in C, N, and O but with low neutron-capture abundances (a CEMP-no star). The metallicities of the stars analyzed span more than 1 dex from [Fe/H] = −3.55 to −2.46. This, combined with a large abundance range of other elements like Ca, Sc, and Ni, confirms that Tuc V is an ultrafaint dwarf (UFD) galaxy. The variation in abundances, highlighted by [Mg/Ca] ratios ranging from +0.89 to −0.75, among the stars demonstrates that the chemical enrichment history of Tuc V was very inhomogeneous. Tuc V is only the second UFD galaxy in which stars located at large distances from the galactic center have been analyzed, along with Tucana II. The chemical diversity seen in these two galaxies, driven by the composition of the noncentral member stars, suggests that distant member stars are important to include when classifying faint satellites and that these systems may have experienced more complex chemical enrichment histories than previously anticipated.